Trace metals and rare earth elements in Rock Oyster Saccostrea cucullata along the east coast of Peninsular Malaysia - Miskon, Mohd Fuad; Shazili, N.A.M.; Mohamad, Faridah (Taylor & Francis, 2013)
Trace metals and rare earth elements (REEs) in the soft tissue of rocky shore Rock Oyster, Saccostrea cucullata, along the east coast of Peninsular Malaysia were determined. Significant inter-spatial variations ( p < 0.05) in trace metals and REEs were recorded. Significant positive correlations ( p < 0.01) were found among REEs concentrations. A few significant correlations were found for trace metals and REEs. Average distribution of metals indicated that Johor State had the highest concentrations compared with Pahang and Terengganu for all metals, except for Pb and Cu. This could most likely be attributed to the highly urbanized and industrialized activities such as sewage discharge. The metal accumulation patterns in the oyster indicated enrichment of essential metals. Sites with relatively high concentrations of the contaminant metals Hg, Cu, Pb and Zn were related to their close proximity to industrial and urban sites or to boating and aquaculture activities. Relative enrichment of Cu, Pb and Zn in oysters in the whole study even from relatively pristine areas is thought to be derived from natural sources as these metals are significantly correlated to REEs distribution. The distribution of REEs show close similarity between all sampling sites, suggesting that they are of similar origins. In all sites, typical saw-tooth chondrite-normalized patterns were observed, which strongly suggested the REEs bioaccumulated in oyster tissues is derived from geogenic sources. Typical deviations from this pattern were found for Ce and Eu and could be explained by their redox chemistry. Results of light to heavy REEs (LREE/HREE) ratios suggested REEs fractionation in coastline marine environment produced more light REEs and less heavy REEs absorbed in the soft tissue of S. cucullata. The ratio of La/Yb in the oyster of 27.3 was remarkably similar to Terengganu River basin soil of 33.0 and to Terengganu River sediment of 27.6. Comparison of metal concentration with maximum permissible limits of toxic metals in food established in different countries, as well as Malaysian Food Act 1983 and Food Regulations 1985 Fourteen Schedule, indicated values were well within safety levels, except for Cu and Zn. Along with its wide distribution on rocky shore areas along the east coast, the present results of trace metals and REEs recorded in soft tissue of S. cucullata collected from 14 sites along the east coast of Peninsular Malaysia served as baseline data for future reference.